Salt acclimation induced salt tolerance is enhanced by abscisic acid priming in wheat - Zongshuai WANG; Xiangnan LI; Xiancan ZHU; Shengqun LIU; Fengbin SONG; Fulai LIU; Yang WANG; Xiaoning QI; Fahong WANG; Zhiyu ZUO; Peizi DUAN; Aizheng YANG; et al. (Plant, Soil and Environment, 2017)
High salt stress significantly depresses carbon assimilation and plant growth in wheat (Triticum aestivum L.). Salt acclimation can enhance the tolerance of wheat plants to salt stress. Priming with abscisic acid (1 mmol ABA) was applied during the salt acclimation (30 mmol NaCl) process to investigate its effects on the tolerance of wheat to subsequent salt stress (500 mmol NaCl). The results showed that priming with ABA modulated the leaf ABA concentration to maintain better water status in salt acclimated wheat plants. Also, the ABA priming drove the antioxidant systems to protect photosynthetic electron transport in salt acclimated plants against subsequent salt stress, hence improving the carbon assimilation in wheat. It suggested that salt acclimation induced salt tolerance could be improved by abscisic acid priming in wheat.